Enhancing Efficient Mathematics Teaching and Learning through Professional Teachers' Standards: The Mediating Role of Technology in Education - Oppong-Gyebi, Emmanuel; Ohene Boateng, Francis (International Journal of Educational Innovation and Research, 2024)
The study analyzed the impact of professional standards on quality teaching and learning strategies among mathematics teachers in Ghana. 365 teachers from selected secondary schools in Greater Kumasi of the Ashanti Region were evaluated using structural equation modelling. The research found that teachers' professional values and attitudes significantly influence their instructional delivery. However, teacher-professional mathematics knowledge and pedagogical practices do not directly impact quality teaching and learning. Technology in education does not mediate between these factors. The study recommends that mathematics teachers be trained in accordance with professional standards through professional learning community workshops on integrating technology into their knowledge and pedagogical practices. The National Teaching Council should emphasize the importance of flexible knowledge acquisition methodologies, embracing instructional risks, and using current intervention tools to improve attitudes towards technology integration and engage in 21st-century teaching with professional standards.